Diferentes usos das terras: distritos de Catalão, Pires Belo e Santo Antônio do Rio Verde, em Catalão (GO) - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The present research in this dissertation is result of observation of growing replacement of typical Cerrado vegetation by pasture and various plantings of exotic cultures in Catalão county. It was made a historical survey searching to understand how Catalão territory has reached its present configuration and what factors make their economic development over the last two centuries. Then, considering the idea of General Systems Theory, was performed the landscape reading aiming understand the historical and environmental factors that facilitated the establishment of land use in Catalão territory currently, as well as which environmental factors contribute to the maintenance of remnant sections of Cerrado within county limits. Through empirical research it was possible to find welldefined land use patterns and that are repeated throughout the county: flat land with extensive agriculture presence; rugged relief lands generally occupied by pasture for cattle breeding and; the remnants of typical Cerrado vegetation was find, as a rule, in environments where the implementation of mechanized agriculture is not favored. Even in sections with native Cerrado remnants, was noticed different degrees of anthropization occasioned usually by cattle breeding in natural and exotic pastures that invade the environments with remaining Cerrado.
Different land uses: Catalão, Pires Belo and Santo Antônio do Rio Verde districts, in Catalão (GO)
Keywords: Catalão (GO); Cerrado; Teoria Geral dos Sistemas; Catalão (GO); Cerrado; General Systems Theory; CIENCIAS HUMANAS::GEOGRAFIA